Optimizing High-Al2O3 Limonite Pellet Performance: The Critical Role of Basicity in Consolidation and Reduction - Yufeng Guo; Yixi Zhang; Feng Chen; Shuai Wang; Lingzhi Yang; Yanqin Xie; Xinyao Xia (Metals)
With the gradual depletion of high-quality iron ore resources, global steel enterprises have shifted their focus to low-grade, high-impurity iron ores. Using low-grade iron ore to produce pellets for blast furnaces is crucial for companies to control production costs and diversify raw material sources. However, producing qualified pellets from limonite and other low-grade iron ores remains highly challenging. This study investigates the mechanism by which basicity affects the consolidation and reduction behavior of high-Al2O3 limonite pellets from a thermodynamic perspective. As the binary basicity of the pellets increased from 0.01 under natural conditions to 1.2, the compressive strength of the roasted pellets increased from 1100 N/P to 5200 N/P. The enhancement in basicity led to an increase in the amount of low-melting-point calcium ferrite in the binding phase, which increased the liquid phase in the pellets, thereby strengthening the consolidation. CaO infiltrated into large-sized iron particles and reacted with Al and Si elements, segregating the contiguous large-sized iron particles and encapsulating them with liquid-phase calcium ferrite. Calcium oxide reacts with the Al and Si elements in large hematite particles, segmenting them and forming liquid calcium ferrite that encapsulates the particles. Additionally, this study used thermodynamic analysis to characterize the influence of CaO on aluminum elements in high-aluminum iron ore pellets. Adding CaO boosted the liquid phase’s ability to incorporate aluminum, lessening the inhibition by high-melting-point aluminum elements of hematite recrystallization. During the reduction process, pellets with high basicity exhibited superior reduction performance.